2016
DOI: 10.17261/pressacademia.2016219820
|View full text |Cite
|
Sign up to set email alerts
|

Work-family conflict in South Asia: the case of Pakistan

Abstract: Financial development in Jordan should be underestimated for two main reasons. First, the total assets of licensed banks constitute about 180 percent of Gross Domestic Product (GDP). Second, the country boasts one of the oldest stock markets in the region. The Amman Securities Exchange (ASE) was established in 1978 and its current capitalization is equivalent to about 75 percent of GDP. Given Jordan's socio-economic challenges, and the fact that successive governments have been suffering from large and consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The study indicated that long working hours and lack of social support are significantly responsible for the work-life imbalance. In the same vein, the study of Syed, Memon, Goraya, Schalk, & Freese (2016) indicate that Pakistani bank employees work for longer hours, as their working hours are not mentioned in the formal contract and are extended beyond the working hours considered as official banking hours. The reason given for the long working hours is "work overload".…”
Section: Determinants Of Work-life Balance In Pakistanmentioning
confidence: 99%
“…The study indicated that long working hours and lack of social support are significantly responsible for the work-life imbalance. In the same vein, the study of Syed, Memon, Goraya, Schalk, & Freese (2016) indicate that Pakistani bank employees work for longer hours, as their working hours are not mentioned in the formal contract and are extended beyond the working hours considered as official banking hours. The reason given for the long working hours is "work overload".…”
Section: Determinants Of Work-life Balance In Pakistanmentioning
confidence: 99%
“…With seemingly endless instant messages, emails and phone calls which have gone beyond the office hours, it is not surprising that knowledge workers will find difficulty in balancing work-life. In Pakistan, where average 48 working hours a week is a common practice and being responsive to clients at work anytime and any day including weekend and public holidays is required has worsened the scenario for knowledge workers (Soomro, Breitenecker, & Shah, 2018;Syed, Memon, Goraya, Schalk, & Freese, 2016). Within values at work, justice (0.377) is found as a leading factor.…”
Section: Degree Ofmentioning
confidence: 99%